2008
DOI: 10.1504/ijtm.2008.019416
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital and business performance in the Portuguese banking industry

Abstract: Previous empirical studies confirm that intellectual capital has a significant and substantive impact on performance. The purpose of this research is to examine the interrelationships and interactions among intellectual capital components and business performance in the Portuguese banking industry. The concept of relational capital was extended to include 'stakeholder orientation' items. Model development and hypothesis testing was conducted using PLS on a sample of 253 respondents from 53 organisations. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
404
1
35

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 364 publications
(474 citation statements)
references
References 91 publications
(86 reference statements)
34
404
1
35
Order By: Relevance
“…The choice of the respondents is consistent with studies by Cabrita and Bontis (2008) and Shabarati et al (2010) who argued that organization characteristics measured were known to selected members in upper echelons, thus they were likely to provide more reliable information. The view of key informant is widely used in human resource management studies (Huselid, Jackson, & Schuler, 1997;Cabrita & Bontis, 2008). The targeted respondents were deemed knowledgeable about issues under investigation for which they are directly responsible.…”
Section: Instrument and Proceduressupporting
confidence: 64%
See 2 more Smart Citations
“…The choice of the respondents is consistent with studies by Cabrita and Bontis (2008) and Shabarati et al (2010) who argued that organization characteristics measured were known to selected members in upper echelons, thus they were likely to provide more reliable information. The view of key informant is widely used in human resource management studies (Huselid, Jackson, & Schuler, 1997;Cabrita & Bontis, 2008). The targeted respondents were deemed knowledgeable about issues under investigation for which they are directly responsible.…”
Section: Instrument and Proceduressupporting
confidence: 64%
“…The researchers established that organizations with high intellectual capital outperform those with low profile of intellectual capital. Similarly, a study by Cabrita and Bontis (2008) on the banking sector in Portugal established a positive significant relationship between intellectual capital and perceptual measures of performance. In addition the results are in line with Fire and Williams's (2003) findings on the relationship between intellectual capital and performance, revealing a negative relationship between intellectual capital (structural, physical, and human capital) and performance of 75 publicly listed companies in South Africa.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Numerous international authors recognise the decisive role of human capital in improving companies' financial performance [CabelloMedina et al, 2011;Jardon, Martos, 2012;Mention, Bontis, 2013], and in increasing their structural and relational capital. This is due to the fact that educated, skilled, and experienced staff tend to establish better relationships with a wide range of partners (thus capitalising on relational assets), and improve the efficiency of business processes (thus generating structural capital) [Cabrita, Bontis, 2008;Kim et al, 2012]. Other authors, on the contrary, insist that relational capital ultimately makes the highest contribution to companies' financial performance [Reed et al, 2006;Huang, Hsueh, 2007;Sharabati et al, 2010]: reliable client and supplier relations allow for cutting costs and increasing sales, thus improving the company's overall competitiveness.…”
Section: Elements Of Intellectual Capital and Companies' Performancementioning
confidence: 99%
“…Another series of studies which have used the telecommunications sector as an example [Garanina, 2010;Suraj, Bontis, 2012] showed that relational capital (a measure of clients' loyalty) may make a critical contribution to such companies' revenues. In turn, [Cabrita, Bontis, 2008] point out that the industry companies specialise in determines the impact that specific elements of intellectual capital make on their performance. Thirdly, the specifically Russian aspects of doing business matter.…”
Section: Main Conclusionmentioning
confidence: 99%